Genome-Wide Analysis of japonica Rice Performance under Limited Water and Permanent Flooding Conditions - Volante, Andrea; Desiderio, Francesca; Tondelli, Alessandro; Perrini, Rosaria; Orasen, Gabriele; Biselli, Chiara; Riccardi, Paolo; Vattari, Alessandra; Cavalluzzo, Daniela; Urso, Simona; Ben Hassen, Manel; Fricano, Agostino; et al. (Frontiers in Plant Science, 2017)
A rice GWAS panel of 281 accessions of japonica rice was phenotypically characterized for twenty six traits related to phenology, plant and seed morphology, physiology and yield for two years in field conditions under permanent flooding (PF) and limited water (LW). A genome-wide analysis uncovered a total of 160 significant marker-trait associations (MTAs), of which 32 were LW-specific, 59 were PF-specific and 69 were in common between the two water management systems. LW-specific associations were identified for several agronomic traits including days to maturation, days from flowering to maturation, leaf traits, plant height, panicle and seed traits, hundred grain weight, yield and tillering. Significant MTAs were detected across all the 12 rice chromosomes, while clusters of effects influencing different traits under LW or in both watering conditions were respectively observed on chromosomes 4, 8 and 12 and on chromosomes 1, 3, 4, 5, 8. The analysis of genes annotated in the Nipponbare reference sequence and included in the regions associated to traits related to plant morphology, grain yield and physiological parameters allowed the identification of genes that were demonstrated to affect the respective traits. Among these, three (OsOFP2, Dlf1, OsMADS56) and seven (SUI1, Sd1, OsCOL4, Nal1, OsphyB, GW5, Ehd1) candidate genes were respectively identified to co-localize with LW-specific associations and associations in common between the two water treatments. For several LW-specific MTAs, or in common among the two treatments, positional co-localizations with previously identified QTLs for rice adaptation to water shortages were observed, a result that further supports the role of the loci identified in this work in conferring adaptation to LW. The most robust associations identified here could represent suitable targets for genomic selection approaches to improve yield-related traits under LW.